Fecal microbiota transplantation and short-chain fatty acids reduce sepsis mortality by remodeling antibiotic-induced gut microbiota disturbances - Lou, Xiran; Xue, Jinfang; Shao, Ruifei; Yang, Yan; Ning, Deyuan; Mo, Chunyan; Wang, Fuping; Chen, Guobing (Frontiers in Immunology, 2023)
Sepsis is the leading cause of death in critically ill patients. It has long been thought that the gastrointestinal tract plays an integral role in the pathophysiology of sepsis. Antibiotic treatment can deplete the commensal bacteria of a patient's gut microbiota and increase their risk of subsequent infections, where gut microbiota dysbiosis may be a key factor. In sepsis, antibiotic therapy significantly destroys the diversity of the gut microbiota, leading to the loss of many beneficial microbes. In this study, we aim to observe whether there is gut microbiota dysbiosis in the early stage of sepsis patients. Then we establish a murine model of sepsis by cecal ligation and puncture (CLP) to study the effects of fecal microbiota transplantation (FMT), and short-chain fatty acids (SCFAs) on gut microbiota, mucosal barrier function, systemic inflammatory response, and survival rate. It is found that FMT and SCFAs can not only reduce mortality and restore the diversity of the gut microbiota in septic mice but can also improve the gut barrier function by reducing epithelial cell pyroptosis, upregulating the expression of tight junction proteins, and reducing intestinal permeability. Furthermore, FMT and SCFAs offer a microbe-mediated survival advantage in a murine model of sepsis, which may be an effective therapy for sepsis.